The role of neutrophils in tPA thrombolysis after stroke: a malicious troublemaker - Li, Qingcan; Ye, Jiao; Li, Zhifang; Xiao, Qinghui; Tan, Senwei (Frontiers in Immunology, 2024)
Acute ischemic stroke represents a critical, life-threatening condition affecting the central nervous system. Intravenous thrombolysis with tissue plasminogen activator (tPA) remains a cornerstone for achieving vascular recanalization in such patients; however, its therapeutic utility is limited, with only approximately 10% of patients benefiting due to the narrow therapeutic window and significant risk of hemorrhagic transformation. Enhancing the efficacy of tPA thrombolysis is therefore imperative. Neutrophils have been identified as key modulators of thrombolytic outcomes, interacting with tPA post-stroke to influence treatment effectiveness. The binding of tPA to low-density lipoprotein receptor-related protein 1 (LRP-1) on neutrophil surfaces induces degranulation and formation of neutrophil extracellular traps (NETs). Conversely, neutrophils impede the thrombolytic action of tPA by obstructing its interaction with fibrin and activating platelets. These findings suggest that targeting neutrophils may hold promise for improving thrombolysis outcomes. This review explores the role of neutrophils in tPA-mediated thrombolysis following acute ischemic stroke, examines neutrophil-associated biomarkers, and outlines potential strategies for enhancing tPA efficacy.